Intima–Media Thickness in Primary Aldosteronism Compared with Essential Hypertension: A Meta-analysis - Muja, Eva; Laçi, Ilirian; Marko, Sonil; Akshija, Ilir (Open Access Macedonian Journal of Medical Sciences, 2024)
AIM: This study was comparison of the intima–media thickness in the primary aldosteronism (PA) patients versus essential hypertension (EH) patients. METHODS: We searched on PubMed for studies about intima–media thickness in PA and found 317 articles. After the title and abstract reading, we excluded 291 studies because they did not fit in our criteria. After the final assessment of the 26 articles, seven of them were chosen as final studies to be included in the meta-analysis. RESULTS: In this study, we included seven studies with a total of participants of 534 patients. The main outcome was a comparison of intima–media thickness between patients with PA, EHs and healthy controls. The result shows a thicker intima media in PA patients in comparison with EH patients and more over with healthy controls, but this was not statistically significant. CONCLUSION: PA predisposes to a thicker intima media in comparison to EH, but we need for larger studies to have significant results.